2010
DOI: 10.3390/s10111022
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of All-Solid-State Chloride Sensors in Synthetic Concrete Pore Solutions

Abstract: Abstract:One type of all-solid-state chloride sensor was fabricated using a MnO 2 electrode and a Ag/AgCl electrode. The potentiometric response of the sensor to chloride in synthetic concrete pore solutions was systematically studied, and the polarization performance was also evaluated. The results show a good linear relationship between the potential reading of the sensor and the logarithm of chloride activity (concentration ranges from 0.05 to 5.0 M), and the potential value remains stable with increasing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…5 shows the calibration of the Fb-Ag/AgCl and PPy-Ag/ AgCl electrodes under alkaline environment in synthetic concrete pore solution contaminated with chloride ions ranging from 0.001 mole per L to 1.0 mole per L. From the gure, it was found that Fb-Ag/AgCl electrode potential shows a uniform variation in the higher chloride concentration region (0.01 mole per L to 1.0 mole per L), forming a linear curve t. At the same time, in the low concentration region (0.001 to 0.01 mole per L) Fb-Ag/AgCl electrode potential was slightly variable from the linear curve, which may be due to the interference of OH À ions, 17 and this deviation could be attributed to the formation of AgOH. 15 On the other hand, the PPy-Ag/AgCl electrode showed a uniform variation in potential at all the chloride ion concentrations.…”
Section: Testing In Various Chloride Concentrationsmentioning
confidence: 91%
See 1 more Smart Citation
“…5 shows the calibration of the Fb-Ag/AgCl and PPy-Ag/ AgCl electrodes under alkaline environment in synthetic concrete pore solution contaminated with chloride ions ranging from 0.001 mole per L to 1.0 mole per L. From the gure, it was found that Fb-Ag/AgCl electrode potential shows a uniform variation in the higher chloride concentration region (0.01 mole per L to 1.0 mole per L), forming a linear curve t. At the same time, in the low concentration region (0.001 to 0.01 mole per L) Fb-Ag/AgCl electrode potential was slightly variable from the linear curve, which may be due to the interference of OH À ions, 17 and this deviation could be attributed to the formation of AgOH. 15 On the other hand, the PPy-Ag/AgCl electrode showed a uniform variation in potential at all the chloride ion concentrations.…”
Section: Testing In Various Chloride Concentrationsmentioning
confidence: 91%
“…16 Ag/AgCl electrodes have become well established over the last decade and have been employed for analytical applications. 17 Gurusami et al reported the use of Ag/AgCl sensors embedded in concrete as reference electrodes and good long-term results were collected over a period of about 4.5 years. 16 The rst attempt in concrete was made in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the stability of the Cl − sensors to pH changes and other major interfering ions (which come from the environment and/or the concrete ingredients) should be assured. There are studies that have evaluated the performance of potentiometric ISEs in monitoring Cl − concentration in concrete [32,[38][39][40][41][42][43][44][45][46][47][48].…”
Section: Potentiometric Chloride Ion Sensorsmentioning
confidence: 99%
“…Based on the findings, the authors claimed that the sensor has excellent chloride sensing ability and well stable in an alkaline medium, and thus it is suitable to monitor Cl − concentration in concrete structure. Gao et al [46] produce all-solid-state Cl − sensor employing MnO 2 and Ag/AgCl electrodes. The potentiometric response and stability of the sensor was examined in synthetic concrete pore solutions with diverse NaCl concentrations ranging from 0.05-5.0 M. The performance of the sensor with the existence of interfering ions of K + , Ca 2+ , Na + , and SO 4 2− was tested.…”
Section: Potentiometric Chloride Ion Sensorsmentioning
confidence: 99%
“…Besides that, the capital related to consumables, service, and labour required by the commercial manufacture is another relevant factor in the design of a commercial ISE [ 21 ]. The literature reports a great variety of chloride ion selective sensors, with different detection principles [ 22 ]. ISEs based on polymeric membranes are of particular interest, since they present potential applications for clinical, environmental, and industrial purposes [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%